2013
DOI: 10.1080/09650792.2013.789719
|View full text |Cite
|
Sign up to set email alerts
|

Creating a ‘third space’ in the context of a university–school partnership: supporting teacher action research and the research preparation of doctoral students

Abstract: The focus of the Education Works Personalization Project was to facilitate teams of teacher action researchers whose goal was to personalize their teaching with the support of university partners including doctoral students in education. The subsequent apprentice-like research experience within this university-school partnership provided an opportunity to study the ways in which teacher action research could serve as a vehicle for bridging the culture gap between schools and universities. Both the research tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 11 publications
0
24
0
4
Order By: Relevance
“…The proliferation of teacher research, by and about teacher researchers, supports his claim yet also depicts how the field has grown more complicated 461 (Cochran-Smith & Lytle, 1999;Leeman & Wardekker, 2013). For example, teacher-led research has been found to provide opportunities for meaningful professional development (Vrijnsen-de Cortea, den Brok, Kamp, & Bergen, 2013), critical thinking (Hagevik, Aydeniz, & Rowell, 2012), discovery learning (Gray, 2013), collaborative collegial learning (Christie & Menter, 2009), university-school partnerships (Arhar et al, 2013;Thornley et al, 2004), and educational policy development (Rust & Meyers, 2006). Cochran-Smith and Lytle (1999) suggest that because teacher research "is such a generative concept, it can be shaped and reshaped to further virtually any educational agenda" (p. 17).…”
Section: Teachers As Researchers: Benefits Challenges and Time An mentioning
confidence: 88%
“…The proliferation of teacher research, by and about teacher researchers, supports his claim yet also depicts how the field has grown more complicated 461 (Cochran-Smith & Lytle, 1999;Leeman & Wardekker, 2013). For example, teacher-led research has been found to provide opportunities for meaningful professional development (Vrijnsen-de Cortea, den Brok, Kamp, & Bergen, 2013), critical thinking (Hagevik, Aydeniz, & Rowell, 2012), discovery learning (Gray, 2013), collaborative collegial learning (Christie & Menter, 2009), university-school partnerships (Arhar et al, 2013;Thornley et al, 2004), and educational policy development (Rust & Meyers, 2006). Cochran-Smith and Lytle (1999) suggest that because teacher research "is such a generative concept, it can be shaped and reshaped to further virtually any educational agenda" (p. 17).…”
Section: Teachers As Researchers: Benefits Challenges and Time An mentioning
confidence: 88%
“…For instance, Arhar et al (2013) describe an undertaking in which teachers acting as action researchers worked closely with university partners, as way to personalize their teaching practices while fostering research collaboration between universities and schools. Other examples include professional learning communities (Cochran-Smith and Lytle 2009) as well as professional development networks Meyers 2006, Fowler andProcter 2008) as sponsors of teacher research for professional learning purposes.…”
Section: Origins and Locations Of Teacher Researchmentioning
confidence: 99%
“…Alsup ( 2006) argues that although the school and the university have different practices in preparing teachers, they are both fundamentally concerned with the development of teacher quality. Notions of boundary can be found in university-school partnership literature (Allen, et al, 2013;Arhar et al, 2013;Smedley, 2001;Tsui & Law, 2007;Waitoller & Kozleski, 2013). For example, drawing on the theoretical framework of activity theory, Tsui and Law (2007) claim that contradictions between supervising teachers and tertiary mentors can be resolved by creating a space where all participants can generate collective knowledge by crossing community boundaries in the professional experience.…”
Section: Working In the 'Boundary Zone"mentioning
confidence: 99%
“…There are examples of partnerships that attempt to close this potential separation as does the Professional Learning Partners Program (Arhar, et al, 2013;Allen, et al, 2013;Douglas & Ellis, 2011;Tsui and Law, 2007;Wilson, 2004). Drawing from CHAT (Engeström, 1987(Engeström, , 2001 and literature in boundary practices (Akkerman& Bakker, 2011;Tuomi-Gröhn & Engeström, 2003), we explore a lens to design a Professional Learning Partners Program which aims to connect schools and university.…”
Section: Creating a Boundary Zone: Professional Learning Partners Promentioning
confidence: 99%